2020
DOI: 10.1101/2020.10.30.362426
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigating epithelial-mesenchymal heterogeneity of tumors and circulating tumor cells with transcriptomic analysis and biophysical modeling

Abstract: Introduction: Cellular heterogeneity along the Epithelial-Mesenchymal Plasticity (EMP) spectrum is a paramount feature observed in tumors and circulating tumor cells (CTCs). High-throughput techniques now offer unprecedented details on this variability at a single- cell resolution. Yet, there is no current consensus about how EMP in tumors propagates to that in CTCs. To investigate a relationship between EMP associated heterogeneity of tumors and that of CTCs, we integrated transcriptomic analysis and biophysi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Other EMT regulators such as TWIST and AP-1 ( Feldker et al., 2020 ) are also reported to drive phenotypic plasticity in melanoma ( Caramel et al., 2013 ; Verfaillie et al., 2015 ). Second, heterogeneity along the EMT axis seen in circulating tumor cells (CTCs) ( Yu et al., 2013 ; Bocci et al., 2021 ) is recapitulated in melanoma CTCs too ( Aya-Bonilla et al., 2020 ). Third, cooperation among phenotypes with varying EMT status has been witnessed during metastasis and tumor formation ( Jolly and Celia-Terrassa, 2019 ), reminiscent of recent observations in melanoma ( Rowling et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other EMT regulators such as TWIST and AP-1 ( Feldker et al., 2020 ) are also reported to drive phenotypic plasticity in melanoma ( Caramel et al., 2013 ; Verfaillie et al., 2015 ). Second, heterogeneity along the EMT axis seen in circulating tumor cells (CTCs) ( Yu et al., 2013 ; Bocci et al., 2021 ) is recapitulated in melanoma CTCs too ( Aya-Bonilla et al., 2020 ). Third, cooperation among phenotypes with varying EMT status has been witnessed during metastasis and tumor formation ( Jolly and Celia-Terrassa, 2019 ), reminiscent of recent observations in melanoma ( Rowling et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to this cluster breakup in the medium, smaller clusters are mainly composed of cells with lower motility, hence are relatively more epithelial-like and the larger clusters are mainly composed of cells with higher motility, and are relatively more mesenchymal-like. This can be a reason for CTCs to be relatively more mesenchymal compared to the primary tumor, as found in the case of Stage II-III breast cancer (GSE111842) [47, 48]. In general, it would be of interest to compare EMT-scores from clusters of different sizes taken from patient blood.…”
Section: Resultsmentioning
confidence: 99%
“…Other EMT regulators such as TWIST and AP-1 (Feldker et al, 2020) are also reported to drive phenotypic plasticity in melanoma (Caramel et al, 2013; Verfaillie et al, 2015). Second, heterogeneity along the EMT axis seen in circulating tumor cells (CTCs) (Bocci et al, 2021; Yu et al, 2013) is recapitulated in melanoma CTCs too (Aya-Bonilla et al, 2020). Third, cooperation among phenotypes with varying EMT status has been witnessed during metastasis and tumor formation (Jolly and Celia-Terrassa, 2019), reminiscent of recent observations in melanoma (Rowling et al, 2020).…”
Section: Discussionmentioning
confidence: 99%